2020
DOI: 10.1021/acs.jpca.0c00102
|View full text |Cite
|
Sign up to set email alerts
|

Bend-to-Break: Curvilinear Proton Transfer in Phenol-Ammonia Clusters

Abstract: The electric field experienced by the OH group of phenol embedded in the cluster of ammonia molecules depends on the relative orientation of the ammonia molecules, and a critical field of 236 MV cm −1 is essential for the transfer of a proton from phenol to the surrounding ammonia cluster. However, exceptions to this rule were observed, which indicates that the projection of the solvent electric field over the O−H bond is not a definite descriptor of the proton transfer reaction. Therefore, a critical electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…The geometries of 126 PhOH-(NH3)n (n=1-10) clusters, calculated using M06-2X/cc-pVTZ method, were reported earlier, 16 and among these 126 structures only 114 structures which show hydrogen bonding between the phenolic OH group to the surrounding ammonia cluster and were considered. 18 These 114 structures were re-optimized using the resolution of identity second-order perturbation theory (RI-MP2) method with cc-pVDZ basis set using ORCA 4.1.2 suite of programs. 20 Following, the electric field along the O-H bond was calculated on the 114 structures using the procedure described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometries of 126 PhOH-(NH3)n (n=1-10) clusters, calculated using M06-2X/cc-pVTZ method, were reported earlier, 16 and among these 126 structures only 114 structures which show hydrogen bonding between the phenolic OH group to the surrounding ammonia cluster and were considered. 18 These 114 structures were re-optimized using the resolution of identity second-order perturbation theory (RI-MP2) method with cc-pVDZ basis set using ORCA 4.1.2 suite of programs. 20 Following, the electric field along the O-H bond was calculated on the 114 structures using the procedure described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…16 In a recent work our group, with the aid of electric field calculations along the donor O-H of phenol in the phenol-(ammonia)n clusters, using at the M06-2X/cc-pVTZ level of theory, has shown that a critical electric field of a critical field of 236 MV cm -1 is essential to transfer of a proton from phenol to the surrounding ammonia cluster. 18 Interesting, Additionally, six exceptions to this rule were observed, which indicates that the projection of the solvent electric field over the O-H bond is not an unqualified descriptor of the proton transfer reaction. Based on these observations, it was noted that the critical electric field is a necessary, but not sufficient condition for the proton transfer process.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[NH3]n clusters. 29,36 Fig. 5 Plots of pKa of the carboxylic acid against the electric field along the O-H group (A) acetic acid and (B) trifluoroacetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ionized and protonated forms of fluoroformic acid have been reported to exist in the gas phase. 36 Moreover, the crystal structure of the anhydrous form of fluoroformic acid has also been reported. 37 Therefore, based on the linear correlation between the pKa and the electric field along the OH group in the carboxylic acid dimer (see Figs 6 and S3) the pKa of fluoroformic acid was estimated to be 0.83 and 1.09 at MP2 and B3LYP-D3 levels of theory, respectively (Table S9, see the SI).…”
Section: Resultsmentioning
confidence: 99%